The Research Capability Of Secondary School Science Teachers - Tolentino, Keneth S. (Future Science / FSH-PH Publications, 2021)
This paper described the perceived level of research capability of secondary school Science teachers in the basic education whereas a descriptive-correlational design was employed to determine the extent of relationship between research capability and profile of the 76 Science teachers from the Schools Division of Pampanga. A Research Capability Self-Assessment Scale Abrazado & Coronel (2016) was adopted to identify the level of research capability of the respondents, also a checklist was developed to identify the problems encountered by on their research undertakings. Most of the Science teachers did not yet pursue higher professional studies. Majority did not have the opportunity to attend research trainings; regarded with low research productivity. Science teachers had moderate research capability. Science teachers’ research capability had low level relationship with their profile in terms of educational attainment, research trainings and seminars attended, and research output. Lack of time, research trainings and research skills were the problems encountered. A sustainable research development program will aid Science teachers to develop and enhance their research capability